Effects of dietary lipid levels on mitochondrial gene expression in low and high‐feed efficient families of rainbow trout Oncorhynchus mykiss. Issue 6 (June 2014) - Eya, J. C.; Yossa, R.; Ashame, M. F.; Pomeroy, C. F.; Gannam, A. L.
Abstract A 2 × 3 factorial study was conducted to evaluate the effects of dietary lipid level on mitochondrial gene expression in mixed sex rainbow trout Oncorhynchus mykiss. Practical diets with a fixed crude protein content of 42%, formulated to contain 10% (42/10), 20% (42/20) and 30% (42/30) dietary lipid, were fed to triplicate groups of either low‐feed efficient (F129; mean ± s.d. = 105·67 ± 3·04 g initial average mass) or high‐feed efficient (F134; mean ± s.d. = 97·86 ± 4·02 g) families of fish, to apparent satiety, twice per day, for 108 days. At the end of the experiment, diets 42/20 and 42/30 led to similar fish condition factors, which were higher than that observed with diet 42/10 (P < 0·05). F134 fish fed diet 42/10 showed the highest hepato‐somatic index, while there was no significant difference among all the other treatments (P < 0·05). When the group of F134 fish fed diet 42/10 was used as the calibrator for gene expression analysis, the five genes selected for their involvement in lipid metabolism (complex I‐nd1, complex III‐cytb, complex IV‐cox1, complex IV‐cox2 and complex V‐atp6) were up‐regulated in the muscle and down‐regulated in both the liver and the intestine. There was a significant family × diet interaction regarding nd1, cox2 and atp6 in the liver; nd1, cytb, cox1, cox2 and atp6 in the intestine, and nd1, cytb, cox1, cox2 and atp6 in the muscle (P < 0·05). The overall results of this study constitute basic information for the understanding of molecular mechanisms of lipid metabolism at the mitochondrial level in fishes.